(untitled) (AYUSHDHARA, 2017)
Even in areas where modern medicine is available, the interest on herbal medicines and their utilization have been increasing rapidly in recent years. Herbal formulations have recently attracted the interest towards versatile application as bioactive components of plants are natural source of medicines to heal various ailments. Herbal cosmetics are formulated, using different ingredients to form the base in which one or more herbal ingredients are used to cure various skin ailments. The present work is to formulate and evaluate the polyherbal ointment comprising Haridra (Curcuma longa), Manjistha (Rubia cordifolia) and Mocharasa (exudate from Salmali malabarica). These drugs have antibacterial, anti-inflammatory, antiseptic, antioxidant, wound healing properties etc. The aqueous extracts were prepared by using traditional method of maceration and Ghana kalpana. The neutral ointment base was prepared and formulation of ointment was done by incorporating the Ghana /extract in the base by Levigation process. Different trials in different proportion of extract and base were performed to obtain stable formulation by levigation and trituration method. Obtained stable formulation was evaluated for its Organoleptic Characters, physicochemical properties like state, color, odor, touch, ease of removal, pH, spreadability, solubility, Loss on Drying, Total ash, Water soluble extractive, Alcohol soluble extract. In toxicological Evaluation, determination of Heavy Metals and Microbial Analysis was done. In these studies, results are obtained within permissible limits and successful stable composition of extracts and base shows synergistic action and there was no evidence of phase separation or irritation and is safe for local application on skin.